Streptococcus Gallolyticus endocarditis in patient with liver cirrhosis: a case report - Aleksandra Radovanovic Spurnić; Ivana Gmizić; Ivana Milošević; Olga Petrović; Danilo Obradović; Arsen Ristić; Olja Stevanović (Journal of Infection in Developing Countries)
Streptococcus gallolyticus (S. gallolyticus) bacteremia is commonly associated with endocarditis and diseases of gastrointestinal tract, especially with colorectal carcinoma. On the other side, it is rarely connected to liver disease, especially alcoholic liver disease. A 44-old patient with a history of one month fever, pre-existing heart murmur and previous alcohol abuse, was treated in Clinic for Infectious and tropical diseases, Clinical Centre of Serbia (CCS), Belgrade. The diagnose of infective endocarditis (IE) of the aortic valve caused by S. gallolyticus has been established. Despite the conducted antibiotic treatment based on antibiogram, pericardial effusion with paracardial aortic abscess was diagnosed on the 9th day of treatment. Pericardiocentesis was done and 800 mL of haemorrhagic fluid was evacuated in the Clinic for Cardiology, CCS. Unfortunately, 20th day of hospitalization the patient died. Clinical autopsy confirmed endocarditis, liver cirrhosis and chronic pericarditis. Prognosis of the outcome of treatment of patient with endocarditis caused S. gallolyticus and liver cirrhosis is not optimistic. Therefore, significant attention should be given to patients with liver cirrhosis and febrile of unknown origin.